Tualang and Kelulut honey reduced Lipopolysaccharides-stimulated inflammatory responses of Microglia - Low, Zhao Xuan; Tan, Kai Li; Keong, Yong Yoke; Looi, Chung Yeng; Ooi, Yin Yin (Universiti Putra Malaysia, 2023)
Microglial activity is crucial in maintaining the central nervous system (CNS) homeostasis. However, prolonged microglial activation have been implicated in the pathology of neurodegenerative diseases. Activated microglia will increase the production of inflammatory cytokines, reactive oxygen species (ROS) and alter their surface marker expression levels. This study used Malaysian honey, Tualang honey (TH), and Kelulut honey (KH) to determine lipopolysaccharide (LPS)-stimulated inflammatory responses of microglia. TH and KH at 0.1 were used in the current study as our findings showed no significant difference in the cell viability between BV2 cells treated with 0.1 of TH and KH and control group. TH and KH reduced the ROS level significantly by 41.62±1.06 and 49.16±0.63, respectively, and slightly reduced the expression of co-stimulatory molecules, CD40 and CD11b in LPS-activated BV2 cells. Our preliminary findings proposed an in-depth future study on the anti-inflammatory effect of TH and KH on microglial activation.